Psychiatry and the Human Condition c y Roberta Passione. - Passione, Roberta; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is the result of extensive archival research conducted on the Collection Silvano Arieti Papers held in the Manuscript Division of the Library of Congress, Washington, D.C. It offers readers the first scientific biography of the renowned Italian-born psychiatrist Silvano Arieti, who in 1939 emigrated to the United States, where he gained fame and recognition for his work on schizophrenia. In 1975, the second edition of his book, Interpretation of Schizophrenia, received the National Book Award in Science. The book has been cast as a twofold journey: an exploration of the life of a psychiatrist and scientist and an overview of twentieth century psychiatry and its significant issues, debates, and transformations. Readers will find useful insights for a better understanding of psychiatry as a discipline capable of portraying the complexity of human nature. .
1. Introduction -- 2. Castaway -- 3. New World -- 4. Roots -- 5. Horizons.-6. Landings -- 7. At the End of the Journey.
Keywords: Psychiatry; Medicine History.; Sociology Biographical methods; Cognitive neuroscience; Psychiatry; History of Medicine; Biographical Research; Cognitive Neuroscience; Community Psychiatry; Social Problems